ANALISIS KEDUDUKAN ANAK HASIL PERKAWINAN CAMPURAN ANTARA WARGA NEGARA INDONESIA DAN WARGA NEGARA ASING - RISTI DWI RAMASARI (Universitas Bandar Lampung (UBL), 2018)
Mixed marriage is basically a marriage conducted by people of different nationalities, one of whom is an Indonesian citizen. The result of a mixed marriage for a child is obtaining the citizenship of the father or from his mother and the child's right to inheritance in the event of a divorce between his parents. The problem of this research is